Pectins of different origin and their performance in forming and stabilizing oil-in-water-emulsions. (April 2015) - Schmidt, U.S.; Schmidt, K.; Kurz, T.; Endreß, H.-U.; Schuchmann, H.P.
Abstract: The effectiveness of different commercially available pectin types in forming and stabilizing oil-in-water-emulsions was investigated. Sugar beet pectin as well as apple and citrus pectins with different degree of methoxylation were tested. In emulsions containing small molecule emulsifiers, all investigated pectins behave similarly. They show stabilizing properties by increasing the viscosity of the aqueous phase. This also influences the effective viscosity ratio of emulsions and it results in the formation and stabilization of submicron droplets. In emulsions without small molecule emulsifiers, the investigated pectins differ in their emulsifying behavior depending on their molecular structure. The higher the amount of covalently bound protein a pectin has, the smaller the characteristic droplet size of the resulting emulsions. Pectins with intermediate degrees of esterification produce the emulsions with the largest characteristic droplet size. Furthermore, differences in the surface activity of pectins were found. Sugar beet and citrus pectins lower the surface tension more than apple pectin. Upon the addition of sucrose, an increase in surface tension is detected but only for sugar beet and citrus pectin solutions. Graphical abstract: Highlights: The performance of different pectin types as oil-in-water emulsifier was evaluated. Differences between formation and stabilization of emulsions are highlighted. Characteristic droplet sizes are correlated with molecular parameters of different pectins. Surface tension values of pectin solutions change upon addition of dry matter.